Small Dysplastic Oral Leucoplakia in a Smoking Woman: a Case Report - Caique Mariano Pedroso; Gustavo Keller Schemberger; João Lucas Dziadzio; Letícia Caroline Condolo; Priscila de Camargo Smolarek (Stilus Optimus, 2021)
Background: Oral leucoplakia is clinical term used to describe white plaques, and that is part of the group of oral potentially malignant disorders. Leucoplakia may show epithelial dysplasia, mainly in harder smoking patient. This case report discusses a small leucoplakia with dysplasia on the tongue's lateral border in a woman, diagnosed early after a routine clinical consultation. Methods: A 57-year-old female patient consulted to the Oral Diagnosis and Surgery Service of the State University of Ponta Grossa, Brazil. First, the patient was referred for the extraction of her lower incisors due to periodontal disease. During clinical examination, was identified a sessile white plaque, of small size, and located on the tongue's left lateral border. Thus, the lesion's diagnostic hypothesis was oral leucoplakia due to patient be chronic smoker for 40 years. The incisional biopsy was performed, with the epithelial tissue and part of the connective tissue removed. Results: The histopathological examination revealed a stratified and keratinized pavement epithelium, with cellular atypia, and presence of hyperchromatism and nuclear pleomorphism. However, the alterations were restricted to the epithelium's basal, characterizing a mild dysplasia. The proposed treatment was surgical removal of the lesion, and the patient was also instructed to quit smoking, as well as she continues to follow-up. Conclusions: The presented case emphasizes the importance of early diagnosis and the orientation of risk factors to smoking patients, even in small lesions that can clinically appear harmless.